The high cost of missing a boat under the Japanese recruitment practices: Timing of regular and non-regular employment after school completion in Japan. (December 2015) - Fong, Eric; Tsutsui, Junya
Highlights: The likelihood of obtaining a regular job drops drastically after the first year. The benefit of investing in additional years of education is quickly diminished within a few years. Gender is not significant to securing a regular job as the first job after school completion. Abstract: We explored the timing of obtaining regular and non-regular employment after school completion in Japan. Our study is based on a unique longitudinal data set, the Japanese Life Course Panel Survey. The results capture a peculiar recruitment system of the Japanese youth labor market. The likelihood of regular employment after school completion in Japan is highly influenced by the number of years after school completion. The likelihood of obtaining a regular job drops drastically after the first year. As job seekers realize that this employment window is closing, they look for non-regular employment. Our study also shows that educational level has a significant effect on the likelihood of overall employment and of regular employment after school completion. However, the effect is quickly diminished within a few years. In other words, the benefit of investing in additional years of education in order to secure a job applies for only a short time. Finally, our study suggests that gender is not significant to securing a regular job as the first job after school completion. Taken together, the results demonstrate how individuals are "channeled" to regular and non-regular employments is related to the unique recruitment system in Japan.